Design of Attendance Recording System for Pilkades Participants Using Web-Based RFID (E-KTP) - Atmiasri; Andris Kosmono, Eko (Program Studi Teknik Elektro Universitas PGRI Adi Buana Surabaya, 2021)
The development of information technology has now been widely used to facilitate, accelerate, and streamline work. The recording system that is still being applied is a type of recording using a manual system using paper media and is inefficient when viewed from a time perspective, recapitulating attendance data and the accuracy or authenticity of the data presented. There is still a frequent habit of voting in the village head elections or not being present at the voting process. Contrary to these problems, this research has developed a recording system using RFID (Radio Frequency Identification) technology. RFID will use sensors to read data. The use of RFID which can make it easier for KPPS officers at TPS. The use of both active and passive RFID technology is able to help record and move data in KPPS, Use of RFID technology, data will be recorded only by passing through a sensor reader on the device, thus the attendance data present by pilkades participants will be stored automatically in storage. So that the attendance of election participants will be easier to do, faster and avoid human error or fraud in the absence of pilkades